Rare case of dural arteriovenous fistula presenting by spontaneous acute subdural hematoma – A case report and review of literature - Golubović, Jagoš; Djilvesi, Djula; Cigić, Tomislav; Papić, Vladimir; Jelača, Bojan; Vuleković, Petar (Vojnosanitetski pregled, 2021)
Introduction. Dural arteriovenous fistulas represent pathological acquired bonds between the meningeal blood vessels (arteries) and drainage veins associated to them. These fistulas can vary in clinical presentations, from being asymptomatic to causing serious neurological deficits, depending mostly on the localization and size. Only one fourth of dural fistulas present themselves with intracranial bleeding. This hemorrhage is most frequently localized in subarachnoid space, occasionally intracerebrally, and seldom beneath the dura mater, ie subdurally. Case report. We presented a rare case of a patient with spontaneous acute subdural hematoma. After the initial treatment and consequent imaging methods, a diagnosis of a dural arteriovenous fistula was established. After the craniotomy for hematoma evacuation, the patient underwent an uneventful endovascular treatment. Despite the rarity of non-traumatic acute subdural hematoma caused by dural arteriovenous fistula, one should not overlook the possible pathogenesis and etiology in patients with spontaneous acute subdural hematoma. Even with the absence of the symptoms and signs of subdural bleeding, dural arteriovenous fistula, as a cause of it, should not be immediately ruled out. Conclusion. Despite the rarity of non-traumatic acute subdural hematoma being caused by dural arteriovenous fistulas, one should not immediately overlook the possible pathogenesis and etiology. Cautious approach is needed when treating such diseases even in the absence of typical symptoms.